Peer review and peer recognition - Doubell, Anton (SA Heart Journal, 2017)
The principle of peer review is critical to the scientifi c contribution made by articles published in a medical journal. Since its inception in 2004 SA Heart has established itself fi rmly as a peer-reviewed cardiovascular journal worthy of the South African Heart Association for which it is the offi cial mouthpiece.